BOUNDARIES AND HORIZONS OF KNOWLEDGE (THE FRONTISPIECE OF F. BACON’S «INSTAURATIO MAGNA») - I. S. Dmitriev; V. P. Krepostnova (Дискурс)
F. Bacon, like many other philosophers of the early modern era, highlighted the importance of artistic representation of his philosophical concepts. F. Bacon’s innovative ideas are revealed not only through actual philosophical narrative, but also through the interpretation of mythological and historical subjects, as well as through the complex symbolism of engravings adorning the title pages of the works of the English philosopher. The famous engraving on the frontispiece of F. Bacon's treatise "Instauratio Magna" (1620) expresses metaphorically the idea of science development project presented in this work. The article regards the symbolism of this engraving and its historical and philosophical contexts.